Millicompost: Sustainable substrate for the production of dragon fruit seedlings (Selenicereus undatus) - de Sousa Antunes, Luiz Fernando; de Sousa Vaz, André Felipe; Santos Reis de Andrade da Silva, Maura [UNESP]; Fernandes Correia, Maria Elizabeth; Ferreira Cruvinel, Fábio; Peres Martelleto, Luiz Aurélio (Elsevier, 2021)
The success of the production of dragon fruit seedlings propagated vegetatively depends on several factors, such as the appropriate choice of the substrate for rooting. It has been verified that the millicompost has contributed to the production of seedlings of some species, however, there are no reports for the dragon fruit. Thus, the objective was to evaluate the efficiency of the millicompost generated by the activity of the diplopods Trigoniulus corallinus in the cuttings of the red dragon fruit. The substrates used were: S1) millicompost, S2) sand + bovine manure and S3) Biomix®. Characterizations of the physical-chemical, chemical, and physical properties of the substrates were carried out. The phytotechnical parameters evaluated in the cuttings of dragon fruit were: number of shoots, length of the largest shoot, fresh and dry masses of the shoot and roots. The millicompost had physicochemical, chemical, and physical properties, promoting greater development of dragon fruit, whose levels of nutrients and physical characteristics, in addition to being superior to the other substrates, were able to provide seedlings of higher quality and size compared to seedlings from the other two substrates tested. The millicompost represents an alternative as an organic substrate in the vegetative propagation of the dragon fruit tree by providing increments of the vegetative characters and biomass production, confirmed by the greater inputs of nutrients accumulated in its plant tissue.
Keywords: Cutting; Dragon fruit tree; millicomposting; Organic substrate; Organic waste; Trigoniulus corallinus